Adherence to All Steps of a Pain Management Protocol in Intensive Care Patients after Cardiac Surgery Is Hard to Achieve. (16th February 2017) - van Gulik, L.; Ahlers, S. J. G. M.; Bruins, P.; Tibboel, D.; Knibbe, C. A. J.; van Dijk, M.
Abstract : Purpose. To investigate adherence to our pain protocol considering analgesics administration, number and timing of pain assessments, and adjustment of analgesics upon unacceptably high (NRS ≥ 4) and low (NRS ≤ 1) pain scores. Material and Methods. The pain protocol for patients in the intensive care unit (ICU) after cardiac surgery consisted of automated prescriptions for paracetamol and morphine, automated reminders for pain assessments, a flowchart to guide interventions upon high and low pain scores, and reassessments after unacceptable pain. Results. Paracetamol and morphine were prescribed in all 124 patients. Morphine infusion was stopped earlier than protocolized in 40 patients (32%). During the median stay of 47 hours [IQR 26 to 74 hours], 702/706 (99%) scheduled pain assessments and 218 extra pain scores were recorded. Unacceptably high pain scores accounted for 96/920 (10%) and low pain scores for 546/920 (59%) of all assessments. Upon unacceptable pain additional morphine was administered in 65% (62/96) and reassessment took place in 15% (14/96). Morphine was not tapered in 273 of 303 (90%) eligible cases of low pain scores. Conclusions. Adherence to automated prescribed analgesics and pain assessments was good. Adherence to nonscheduled, flowchart-guided interventions was poor. Improving adherence may refine pain management and reduce side effects.